(untitled) (Sains Humanika, 2022)
Service learning is a learning approach that gives students the opportunity to practice the knowledge gained to their application in a real situation / reality. Service learning activities can support better student understanding and give students the opportunity to more clearly visualize theoretical to practical concepts. Therefore, in courses that require the implementation of learning concepts into practice, the integration of Service Learning activities is appropriate so that students have the opportunity to gain a meaningful learning experience. Therefore, in learning the Computer Network course, service learning activities are integrated together so that students can better visualize the theoretical concepts to their applications in the real world. However, in support of better visualization of students, the activities in the learning process also require the appropriate use of visuals as stated by McLoughlin & Krakowski (2001). According to him, there are three elements in supporting the continuum of students’ visualization thinking, namely the first element of visual thinking, the second element of visual learning, and the third element of visual communication. Based on the stages in the visualization thinking continuum, this study identifies the student’s level of visualization and then highlights the change pattern of the student’s visualization thinking continuum towards the implementation of service learning in the Computer Network course. In addition, this study also obtains students’ perceptions of the implementation of service learning activities with learning activities that promote the development of students’ continuum of visualization thinking. Through the design of a quasi-experimental study involving quantitative data and qualitative time series data, a total of 55 respondents consisting of undergraduate students who are currently following the Computer Networking course have been selected as the sample of this study. Data is obtained based on scoring rubrics, questionnaires, interviews and observations throughout the activity. The findings of the study through a paired t-test, show that there is a significant difference between the average pre-score and post-score (p<0.05) for each element. Meanwhile, the results of the study on students’ perceptions of service learning show that students agree that service learning can improve knowledge (average=3.75) and skills (average=3.5) in learning Computer Networking courses. In conclusion, the integration of Service Learning activities is able to support the improvement of students’ visualization thinking continuum level and directly give good understanding to students.